Jesus “The Way” According to Origen and Marcellus: Confronting Two Patristic Traditions - Fernández Eyzaguirre, Samuel (Religions, 2021)
The article aims to examine and compare the evangelic title of Jesus the Way (John 14:6) in two Christian authors who belonged to two opposing theological traditions, namely, Origen of Alexandria and Marcellus of Ancyra. This comparison, based on original texts, aims not only to show the differences between these two patristic traditions, but rather to identify some common traits that belong to the core of Christian faith. Thus, Origen of Alexandria and Marcellus of Ancyra, two very dissimilar Christian authors, were of the same mind in confessing that only if the Son of God became fully human, could he be the Way for humankind towards the Father.